Barriers faced by undergraduate dental students when conducting research: a qualitative study - Mohammed Mahmoud Sarhan; Lama Nasser Aljohani; Raghad Ibrahim Alsaleh; Roze Abdulaziz Mubaraki; Malak Abdulaziz Almozaen; Rimas Sabih Alharbi (BMC Medical Education)
Abstract Background Research is an important part of dental education. While several quantitative studies have examined the barriers that undergraduate dental students face when conducting research, qualitative studies exploring the details and contexts of these barriers are rare. To bridge this gap, this research qualitatively explores the barriers faced by undergraduate dental students when conducting research. Methods The present qualitative study employs what is known as the “performative knowledge strategy.” The 14 study participants were dental trainees included 10 undergraduate students and 4 interns who participated in research projects that were not part of their mandatory curriulum requirements. Diaries and semi-structured virtual (online) interviews were used to collect the data. Finally, using an inductive strategy, a thematic analytical approach was conducted to analyze the data. Results Six key themes emerged from the data analysis. The themes of “inadequate knowledge,” “time constraints” and “lack of resources” confirm and align with the findings of previous studies, while the themes “misaligned schedules,” “delayed response” and “lack of orientation” represent new insights into the barriers to research faced by undergraduate dental students. Conclusion This study identified six factors that posed substantial barriers to research by undergraduate dental students. Analysis of these barriers can lead to the design and implementation of strategies to enhance and improve research experience. Additional qualitative research in this area would help to reveal further details of the barriers to research, while additional quantitative studies are required to assess the frequency and trends of the newly revealed barriers. Clinical trial number Not applicable.